Threshold Concepts in the Discipline of Pharmacology - A Preliminary Qualitative Study of Students’ Reflective Essays - Faraz Khurshid; Babu Noushad; Dean Whitehead (Health Professions Education, 2020)
Purpose: Pharmacology is widely experienced as a difficult to learn discipline. Unfamiliarity with its technical and medical terms, and how pharmacological principles transfer from theory to practice, is especially troublesome. This known state of affairs is even more compounded where English is not the first language of students in question. This study aimed to discern the crucial aspects of health science students’ reflections from an Eastern – Mediterranean context on the learning and practice of pharmacology using threshold concept framework. Methods: 21 students enrolled in the pharmacology component of a four years’ undergraduate optometry program were recruited for this study. They were provided with prompts and guidelines to write reflective essays related to their learning – teaching experience of pharmacological concepts and constructs in preparation for clinical practice. Results: The reflective qualitative accounts were thematically analysed using a recent version of NVivo©. The themes were cross-referenced against two main criteria of threshold concept framework which included transformation and troublesomeness. The key characteristics that eventuated was transformation - in that students felt they had transformed into students who could learn and master. Discussion: This study observed that learning process, when accompanied by challenges such as difficulty in understanding ‘foreign’ concepts and overwhelming content, motivated the students to adopt various strategies that not only aided their understanding of the subject but also transformed them as learners. The key attribute of threshold concept framework that thematically emerged through this study included transformation; in that students felt they had transformed into persons who could learn (and master) pharmacology alongside ‘creative’ teaching methods and ‘working out’ individual coping strategies.